ANALYSIS OF THE INFLUENCE OF PROFITABILITY, LIQUIDITY, AND SOLVENCY AGAINST THE PRICE SHARE BEFORE & AFTER PANDEMIC COVID-19 (STUDIES CASE COMPANY HEALTHCARE SECTOR WHICH REGISTERED IN BEI) - R. Enough Bhaktiar; Achirsyah Bahar; Widi Wulandari Gunawan (Jurnal Scientia, 2023)
This study aims to analyze how the differences in the effect of profitability, Liquidity, and Solvability in Stock Prices before and during the covid-19 virus pandemic in Healthcare sector of companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 – 2020. This type of research is a quantitative comparative study. Determination of the sample using purposive sampling technique. The number of samples in this study were 16 companies that met the criteria. The research method used in this research is descriptive statistical method. Statistical analysis used is classical assumption test, multiple regression analysis, hypothesis testing using F test, coefficient of determination test, paired sample t – Test (T test), and Wilcoxon Signed Rank Test using SPSS 25 measuring instrument. Based on the results of the study, it shows that Profitability as proxied by Return On Assets (ROA) has no different effect on share prices of Healthcare sector companies before and after the Covid-19 pandemic. Meanwhile Liquidity US proxyed by the Current Ratio (CR) and Solvability US proxyed by The Debt to Equity Ratio (DER) there are differences in the effect on share prices of the Healthcare sector companies before and after the Covid-19 pandemic.